Techniques for Assessment of Vertical Spray Pattern: A Review - , D. Srigiri; Sushilendra,; , Sunil Shirwal; , Vijayakumar Palled; , A. G. Sreenivas; , Pampanna Y (Archives of Current Research International, 2025)
This paper reviews various techniques for assessing vertical spray patterns. Determination of spray characteristics is one of the most important tasks in the development of the sprayer. Uneven spray characteristics will result in loss of pesticide in the form of drift and wastage of chemicals. Many of the horizontal patternators are available to test the nozzle for field crops. Orchard crops often have varying canopy heights and densities, which can lead to uneven spray distribution if not properly managed. By evaluating the vertical spray pattern, farmers can adjust sprayers to match the specific characteristics of the canopy, reducing pesticide waste, minimizing environmental impact, and improving coverage in the target areas. The different techniques for assessing spray patterns include image analysis of water-sensitive papers, analysis of droplets by laser or ultrasonic techniques, computational fluid dynamics, thermography and vertical patternators.